Overcoming roadblocks for in vitro nurseries in plants: induction of meiosis - Cook, Tanner M.; Isenegger, Daniel; Dutta, Somak; Sahab, Sareena; Kay, Pippa; Aboobucker, Siddique I.; Biswas, Eva; Heerschap, Seth; Nikolau, Basil J.; Dong, Liang; Lübberstedt, Thomas (Frontiers in Plant Science, 2023)
Efforts to increase genetic gains in breeding programs of flowering plants depend on making genetic crosses. Time to flowering, which can take months to decades depending on the species, can be a limiting factor in such breeding programs. It has been proposed that the rate of genetic gain can be increased by reducing the time between generations by circumventing flowering through the in vitro induction of meiosis. In this review, we assess technologies and approaches that may offer a path towards meiosis induction, the largest current bottleneck for in vitro plant breeding. Studies in non-plant, eukaryotic organisms indicate that the in vitro switch from mitotic cell division to meiosis is inefficient and occurs at very low rates. Yet, this has been achieved with mammalian cells by the manipulation of a limited number of genes. Therefore, to experimentally identify factors that switch mitosis to meiosis in plants, it is necessary to develop a high throughput system to evaluate a large number of candidate genes and treatments, each using large numbers of cells, few of which may gain the ability to induce meiosis.